Socialization of Coastal and Marine Geohazard of Makassar City Coastal Tourism Area - Rachman, Taufiqur; ., Juswan; Paroka, Daeng; Baeda, Achmad Yasir; Rahman, Sabaruddin; Paotonan, Chairul; Umar, Hasdinar; Alie, Muhammad Zubair Muis; ., Ashury; Husain, Firman; Assidiq, Fuad Mahfud (Faculty of Engineering UNHAS, 2023)
Coastal and marine geohazard threats can occur in coastal tourism areas in Makassar City. Several coastal tourism sites in Makassar City are managed by the community, namely by the Tanjung Merdeka Community Empowerment Agency (LPM) and acts as a partner for socialisation activities. Tourism managers are still ignorant of the potential for coastal and marine geohazards, such as the lack of information on geohazard signs and the potential for accidents that lead to disasters for tourism visitors. Socialisation of coastal and marine geohazards in Makassar City's coastal tourism areas has been carried out with an increase in the average knowledge of participants by 45.3%. The increase in partner knowledge includes awareness, preparedness, and disaster response attitudes about coastal and marine geohazard phenomena in coastal tourism activities, which can ultimately encourage and realise partners as community-based tourism managers who implement early warning of disaster risk and occupational safety. Strengthening partners is realised by handing over coastal and ocean geohazard signs as an early warning of disasters that can occur at tourist sites.